THE INFLUENCE OF USING CLIMBING GRAMMAR MOUNTAIN GAME TOWARDS STUDENTS’ SIMPLE PAST TENSE MASTERY (A Pre-Experimental Study to the Ninth Grade Students of Junior High School 01 in Mempawah Hilir in the Academic Year of 2019/2020) - Febry Wulan Pangesti; Aunurrahman Aunurrahman; Yulia Ramadhiyanti (IKIP PGRI Pontianak, 2021)
This research used pre-experimental research that wanted to know whether Climbing Grammar Mountain Games has effect to teach simple past tense to the ninth grade students of JHS 01 Mempawah Hilir in Academic Year 2019/2020. This research used cluster random sampling, the researcher used multiple choice as the tool of data collection, but before it the researcher did the try out to find out which sentences that could be used as the tool by using validity test. After getting the valid questions for pre-test and post-test, then the mean score of pre-test and post-test would be compared. The result mean score from pre-test was 45.71 and from post-test was 67.32. The calculated of t-test showed that tobtain was higher than ttable, it was 17.491.703, It means that the testing hypothesis was accepted. Also supported by the result of effect size was 3.77, it had strong effect to this research. Therefore, Climbing Grammar Mountain Game is suggested to teach simple past tense. Keywords: simple past tense, climbing grammar mountain game, experimental